Following the Customers: Dynamic Competitive Repositioning - Ning, Z. Eddie; Villas-Boas, J. Miguel (Management Science, 2022)
We consider dynamic repositioning when competing firms try to follow the evolution of consumer preferences while taking into account the competitive interaction, both in terms of static market competition and the dynamic effects of different firm positionings. We fully characterize the dynamic market equilibrium, which includes the timing of the firms’ repositionings depending on consumer preferences. As consumer preferences evolve away from where both firms are located, one firm first moves to follow consumer preferences, with the second firm only moving if the consumer preferences continue evolving away from that firm. The model predicts rich market dynamics, where firms stay for some period in different positionings if consumer preferences are in a relatively middle ground or where a firm repositions to follow consumer preferences but then repositions back to the original position if consumer preferences return. We find that, when the variability of the consumer preferences or the discount rate is greater or when the importance of the repositioning attribute is smaller, firms are less likely to follow consumer preferences. Firms are more heterogeneous in their responses, which leads to longer periods of differentiation when the variability of the consumer preferences, the discount rate, or the importance of the repositioning attribute increases. We also find that competing firms reposition less frequently than what is socially optimal and what collusion would imply, and we find more differentiation under collusion than under competition. This paper was accepted by Matthew Shum, marketing.